Rebellion in the Backlands: Landscape with Figures - Galvão, Walnice Nogueira (ABEI Journal, 2010)
Brazil’s historical situation in the period immediately preceding the writing of Os Sertões informs the very conception of the book. The Republic was proclaimed in 1889, one year after the abolition of slavery, and the early years of republican period were marked by a number of more or less serious and protracted insurrections, as well as small local uprisings. It took some time for the new regime to consolidate and begin to function properly. The Canudos War, which took place in the hinterland of Bahia in 1896-1897, is just one among the various revolts that punctuated the period of transition. Os Sertões is a chronicle of this historical event, to which the author was an eyewitness.